48.2: Invited Paper: Full Color Video Electrowetting E‐paper Display. (24th February 2021) - Henzen, Alex; Zhou, Guofu; Guo, Yuanyuan; Dou, Yingying; Jiang, Hongwei; Yang, Guisong; Tang, Biao
Abstract : E‐paper technology has evolved slowly since the introduction of monochrome electrophoretic displays. Grayscale electrophoretic displays are still limited to 16 levels of grey and update speed has not significantly improved. Color versions are either dark or even slower to update. The key to breaking this impasse lies in a technology that can provide fast switching, and provide a sufficiently large, transmissive aperture. We have built a multilayer electrowetting display, providing acceptable resolution (648 × 480) for a 6″, 262k color video e‐paper display.